SYNTHESIS OF 5 H-IMIDAZO [1, 2-a] THIOPYRAN0-[4', 3': 4, 5] THIEN0[2, 3-d] PYRIM1DIN-5-0NE (Biological Sciences - PJSIR, 2001)
The enamino-ester, ethyl, 2-amino-4,7-dihydro-5H-thieno[2,3-c]thiopyrano-3-carboxylate (5) was prepared from tetrahydrothiopyran-4-one (4). Annelating reagent, 5-methyl-2-methylthioimidazoline (8) was prepared starting from J , 2-diaminopropane (6) via 5-methyl-2-imidazolidinethione (7). The reaction of enamino-ester (5) with the annelating reagent (8) i n HMPTA leaded to new 1, 2, 3, 6, 7, 9-hexahydro-5H-imidazo[ I , 2-a]thiopyrano[4', 3':4, 5]thieno-[2, 3- d]pyrimidin-5-one (9) in good yield.